Gilles de La Tourette's Syndrome - Chairul Yoel; A. Afif Siregar; A. H. Sutanto (Paediatrica Indonesiana, 1984)
A case of Gilles de Ia Tourette's Syndrome is presented. This is the second reported case in Indonesia. The diagnosis was based on four essential features : childhood onset, multiple motor tics, vocal tics and changing pattern of the symptoms. The exact etiology of this syndrome is still unknown. It is proposed that patients with this illness could have hyperactivity of the dopaminergic systems in their basal ganglia. Symptomatic improvement has been achieved with haloperidol. The response to this drug could not be evaluated in this patient because of refusal to continue the treatment.